INVESTIGATION OF RATIONAL BUBBLES AND VOLATILITY SPILLOVERS IN COMMODITY MARKETS: EVIDENCES FROM PRECIOUS METALS - İsmail Çelik; Hilmi Tunahan Akkuş; Nazlıgül Gülcan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Price bubbles which can be expressed as thedeviation of the price of an asset from its fundamental value, have significantimpacts on markets. The effects of the financial crisis that started with theburst of the housing bubbles in the USA in 2008 have spread all over the worldand turned into a global crisis. In this study, the price bubbles of gold, silver,platinum and palladium in the commodity markets for the period between01.01.2010-19.02.2019 were investigated. RtADF, SADF and GSADF methods wereused to determine the formation and burst periods of price bubbles. As a resultof the analysis, price bubbles were found in gold, silver and platinum, whereasno bubbles were found in palladium prices. Due to the close formation dates ofthese bubbles, whether there was any return or volatility spillover betweengold, silver and platinum markets was investigated with VAR-EGARCH method. As aresult of the study, it was found that there was a multiple spillover betweenthe gold, silver and platinum returns. Thus, it was concluded that the pricebubbles formed in precious metals triggered each other. Findings regarding thepresence of price bubbles in the precious metal markets are crucial for tradersin terms of trading timing. However, the findings related to the volatilityspillover among precious metals are also important in terms of considering theeffect of this spillover for the investors who provide hedging by preciousmetals.